RETRACTED: Oncoproteins of High-Risk HPV and EBV Cooperate to Enhance Cell Motility and Invasion of Human Breast Cancer Cells via Erk1/Erk2 and β-Catenin Signaling Pathways - Gupta, Ishita; Jabeen, Ayesha; Vranic, Semir; Al Moustafa, Ala-Eddin; Al-Thawadi, Hamda (Frontiers in Oncology, 2021)
Breast cancer is a leading cause of death in women around the world. Most breast cancer-related deaths are a result of complications from the metastatic spread. Several recent studies reported that high-risk human papillomaviruses (HPVs) and Epstein–Barr virus (EBV) are co-presented in different types of human carcinomas including breast; however, the cooperative effects between high-risk HPVs and EBV oncoproteins in human breast cancer have not been investigated yet. Thus, we herein explored the cooperation outcome between E6/E7 and latent membrane protein 1 (LMP1) oncoproteins of high-risk HPV type 16 and EBV, respectively, in two human breast cancer cell lines, MCF7 and MDA-MB-231. Our data revealed that the cooperation of E6/E7 and LMP1 oncoproteins stimulates cell proliferation and deregulates cell cycle progression of human breast cancer and normal mammary cells; in parallel, we noted that E6/E7/LMP1 incite colony formation of both breast cancer cell lines but not normal cells. More significantly, our results point out that the co-expression of E6/E7 and LMP1 oncoproteins enhances cell motility and invasion of MCF7 and MDA-MB-231 cell lines; this is accompanied by deregulation of epithelial–mesenchymal transition biomarkers including E-cadherin, β-catenin, fascin, and vimentin. The molecular pathway analysis of HPV and EBV oncoproteins cooperation shows that it can enhance the phosphorylation of extracellular signal-regulated kinases (Erk1/Erk2) in addition to β-catenin, which could be behind the effect of this cooperation in our cell models. The study clearly suggests that high-risk HPV and EBV coinfection can play an important role in breast cancer progression via Erk1/Erk2 and β-catenin signaling pathways.